2004
DOI: 10.4049/jimmunol.173.9.5810
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Ligand 18, An Atopic Dermatitis-Associated and Dendritic Cell-Derived Chemokine, Is Regulated by Staphylococcal Products and Allergen Exposure

Abstract: Atopic dermatitis is a chronic inflammatory skin disease with a steadily increasing prevalence. Exposure to allergens or bacterial superantigens triggers T and dendritic cell (DC) recruitment and induces atopic skin inflammation. In this study, we report that among all known chemokines CCL18/DC-CK1/PARC represents the most highly expressed ligand in atopic dermatitis. Moreover, CCL18 expression is associated with an atopic dermatitis phenotype when compared with other chronic inflammatory skin diseases. DCs ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 37 publications
(39 reference statements)
5
117
4
Order By: Relevance
“…Moreover, CCL18 expression is also detected in atherosclerotic lesions (21). In monocytes in vitro its production is induced by LPS and CD40L (53), whereas in iDC it is activated by anti-inflammatory stimuli such as IL-10 or vitamin D 3 (54,55). Since rodents do not have a CCL18 analog, studies on its regulation and function in vivo have been hampered (19).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, CCL18 expression is also detected in atherosclerotic lesions (21). In monocytes in vitro its production is induced by LPS and CD40L (53), whereas in iDC it is activated by anti-inflammatory stimuli such as IL-10 or vitamin D 3 (54,55). Since rodents do not have a CCL18 analog, studies on its regulation and function in vivo have been hampered (19).…”
Section: Discussionmentioning
confidence: 97%
“…However, CCL18 is the most highly expressed ligand specific to AD with levels in the lesional skin reported to be 100 fold higher than CCL17. 115 The regulation of CCL18 by allergen exposure and microbial products suggest a crucial role for this chemokine in the initiation and amplification of atopic skin inflammation. 115,120 Further, CCL1-CCR8 mediated recruitment has been shown to play a role in DC-T cell interactions at the sites of atopic skin inflammation.…”
Section: B Effector Cytokines and Chemokinesmentioning
confidence: 99%
“…115 The regulation of CCL18 by allergen exposure and microbial products suggest a crucial role for this chemokine in the initiation and amplification of atopic skin inflammation. 115,120 Further, CCL1-CCR8 mediated recruitment has been shown to play a role in DC-T cell interactions at the sites of atopic skin inflammation. Further work will delineate whether targeting these molecules might provide therapeutic benefit.…”
Section: B Effector Cytokines and Chemokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…As further discussed below, CCR4 and CCR10 ligands cooperate in the recruitment of memory T cells to sites of skin inflammation (Mirshahpanah et al, 2008;Reiss et al, 2001). The human chemokine CCL18 is one of the most highly expressed chemokines produced by DC in lesional skin of AD patients but not in psoriasis (Fujita et al, 2011;Gros et al, 2009;Pivarcsi et al, 2004). Pivarcsi et al showed that allergen exposure, as well as staphylococcal products induced its expression in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%